Pemenuhan Kebutuhan Energi dalam rangka Mewujudkan Ketahanan Nasional - Gde Pradnyana (Jurnal Maksipreneur, 2016)
Indonesia has the potential vulnerability enormous energy availability. From the supply side, Indonesia has not showed the synergy between the depletion of oil and gas on a large scale with the search for new sources of its reserves. Searching new reserves abroad also yet to show tangible results and not get full supported from the government. Meanwhile, shares of oil and gas is still a very big role in the national energy mix of Indonesia up to 25 years to come. The government also has not succeeded in converting the results of oil and gas into industrial assets. Prioritizing local-content policy produces only rents of business that would increase the cost of production and distribution of oil and gas to the people.